A link between urease and polyamine metabolism in Cryptococcus neoformans. (September 2021) - Toplis, Barbra; Bosch, Caylin; Stander, Marietjie; Taylor, Malcolm; Perfect, John R.; Botha, Alfred
Abstract: The urease enzyme of Cryptococcus neoformans is linked to different metabolic pathways within the yeast cell, several of which are involved in polyamine metabolism. Cryptococcal biogenic amine production is, however, largely unexplored and is yet to be investigated in relation to urease. The aim of this study was therefore to explore and compare polyamine metabolism in wild-type, urease-negative and urease-reconstituted strains of C. neoformans . Mass spectrometry analysis showed that agmatine and spermidine were the major extra- and intracellular polyamines of C. neoformans and significant differences were observed between 26 and 37 °C. In addition, compared to the wild-type, the relative percentages of extracellular putrescine and spermidine were found to be lower and agmatine higher in cultures of the urease-deficient mutant. The inverse was true for intracellular spermidine and agmatine. Cyclohexylamine was a more potent polyamine inhibitor compared to DL-α-difluoromethylornithine and inhibitory effects were more pronounced at 37 °C than at 26 °C. At both temperatures, the urease-deficient mutant was less susceptible to cyclohexylamine treatment compared to the wild-type. For both inhibitors, growth inhibition was alleviated with polyamine supplementation. This study has provided novel insight into the polyamine metabolism of C. neoformans, highlighting the involvement of urease in biogenic amine production. Graphical abstract: Image 1 Highlights: Agmatine and spermidine are major polyamines of C. neoformans Cryptococcal spermidine is potentially produced via agmatine Cryptococcal polyamine metabolism is influenced by temperature Urease is linked to biogenic amine metabolism in C. neoformans